The Impact of Overcrowding on the Histopathology of Catfish Organs in Aquaculture Systems - Farida, Mia Nur; Widyarini, Sitarina; Kristianingrum, Yuli Purwandari; Sutrisno, Bambang; Sugiyono, Sugiyono; Akrom, Afif Muhammad (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2026)
Overcrowding is a major environmental stressor in confined-container fish farming systems. This condition can degrade water quality and trigger stress responses that damage the fish's internal organs. This study aimed to analyze the effect of stocking density on histopathological changes in the gills, liver, spleen, and kidney of catfish (Clarias sp.). Fish were reared for 30 days at four different stocking densities: 10, 20, 30, and 40 individuals per bucket (50 L). Histopathological examination used Hematoxylin–Eosin staining. The results showed that increasing stocking density correlated strongly with lesion severity. The gills exhibited epithelial hyperplasia and lamella fusion, kidneys exhibited hydropic degeneration, and the spleen showed increased melanomacrophage centers (MMCs) and white pulp depletion. These findings confirm that overcrowding causes significant damage to catfish's vital organs, thus high stocking densities are not recommended for confined-container fish farming systems.